The Interpretation of Cultures: Geertz Is Still in Town - Simon Susen (Sociologica, 2024)
Clifford Geertz’s The Interpretation of Cultures (1973) is widely regarded as one of the most important contributions to the humanities and social sciences in general and anthropology in particular. On its 50th anniversary, the literature drawing on this monumental work is so vast that it is hard to see how anything of significance may still be added to the wide range of insights gained from the in-depth engagement with its main argument. The noticeable differences in opinion between followers and detractors of Geertz’s project notwithstanding, most commentators will agree that The Interpretation of Cultures, having dominated the agenda of Anglophone anthropology for at least two decades after its publication, has had a major and lasting impact on neighbouring disciplines and subdisciplines — notably sociology, social psychology, politics, history, philosophy, and cultural studies. This paper aims to demonstrate that the key conceptual components of Geertz’s enterprise can be located in his case for an interpretive theory of culture, epitomized in the methodological commitment to providing a ‘thick description’. The first half of this paper comprises an inquiry into the core assumptions underlying Geertz’s defence of this endeavour, before moving, in the second half, to an assessment of some controversial issues arising from his approach.